Hizbut Tahrir Malaysia: the Emergence of a New Transnational Islamist Movement in Malaysia - Osman, Mohamed Nawab Mohamed (Al-Jamiah: Journal of Islamic Studies, 2009)
This paper looks at the Hizbut Tahrir of Malaysia and places it in the context of the wider and deeper development of Muslim politics and mass mobilisation across Asia and the world at large. While much has been written about the Hizbut Tahrir of Indonesia (HTI), little is known about the HTM. This paper traces the initial arrival of the HT to Malaysia, via the network of Malaysian students and activists who were educated abroad and who have managed to build their own inter-personal networks and relationships outside the parameters of mainstream political Islam and the state apparatus in the country. Furthermore it is interesting to note that HTM in Malaysia takes its own unique stand on Islamic issues with relation to the mainstream Islamic party PAS and the Malay-Muslim UMNO party. The paper therefore attempts to locate the ideological positioning of the HTM in the wider context of Islamist politics in contemporary Malaysia and to analyse its relationship to the wider currents of ethno-communal as well as religious politics in the country as a whole.